INFLUENCE OF BIOMASS Lemna sp. ON THE PHYSICAL PARAMETERS OF PEAT WATER IN THE REARING MEDIUM OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) - Willy Josevin Manihuruk; Saberina Hasibuan; Rodhi Firmansyah (Asian Journal of Aquatic Sciences, 2026)
Peatland waters hold great potential for aquaculture development; however, their unfavorable characteristics, such as low pH, brownish water color, and high levels of Total Dissolved Solids (TDS) and Total Suspended Solids (TSS), pose major challenges. One approach to improving peat water quality is the use of aquatic plants as phytoremediation agents, such as Lemna sp. This study aims to determine the effect of Lemna sp biomass on the physical parameters of peat water and to identify the optimal biomass for the rearing of Asian redtail catfish (Hemibagrus nemurus). The study was conducted from March to July 2025 at the Integrated Marine Science Laboratory of the Faculty of Fisheries and Marine Sciences at the Universitas Riau. The research method used was an experiment with a one-factor completely randomized design (CRD), consisting of five Lemna sp biomass treatments (0, 25, 37.5, 50, and 62.5 g/m²) and three replicates. The parameters observed included TDS, TSS, turbidity, temperature, pH, water color, absolute weight gain, and survival rate of Asian redtail catfish. The results showed that the addition of Lemna sp biomass significantly improved (P<0.05) the physical parameters of peat water. Increasing the Lemna sp biomass reduced TDS and TSS values and improved water clarity compared to the control without Lemna sp. These improvements in water quality positively affected the absolute weight gain and survival rate of Asian redtail catfish during the rearing period. A Lemna sp. biomass of 62.5 g/m² yielded the best results, with the most optimal physical quality of peat water and the highest growth and survival rates of Asian redtail catfish.